Green synthesis of DyBa2Fe3O7.988/DyFeO3 nanocomposites using almond extract with dual eco-friendly applications: Photocatalytic and antibacterial activities. (12th April 2022) - Mahdi, Makarim A.; Yousefi, Seyede Raheleh; Jasim, Layth S.; Salavati-Niasari, Masoud
Abstract: For the first time, photocatalytical and antibacterial activities of DyBa2 Fe3 O7.988 /DyFeO3 (Dy-Ba-Fe-O) nanocomposites as eco-friendly applications of this compound was studied in the same time. Since the applications of this compound are eco-friendly, ultrasound technique was chosen as the synthesis method. Achieving the pure product with good crystallinity with the lowest energy consumption can be considered as one of the advantages of this work. Using the almond core extract as a natural reagent was another reason for consideration this method as a green process. Band gap of this nanocomposite was estimated about 2.6 eV that showed this product can be used as a visible-active photocatalyst. Rhodamin-B dye as an organic pollutant model using the as-prepared nanocomposite was degraded about 72% that was a considerable result under visible irradiation. Elimination of microorganisms was studied by disc diffusion to recognize the sensitivity of bacterial ( Staphylococcus aureus, Bacillus subtilis, E. coli, K. pneumonia and P. aeruginosa ) strains the manufactured. The results confirmed that DyBa2 Fe3 O7.988 /DyFeO3 (DBFeO) nanocomposites can be used as an antibacterial agent because of the manifested strong antibacterial ability upon Gram-negative pathogens such as K. pneumonia and E. coli . The properties of this product were characterized by different analyses including SEM, XRD, EDS, FT-IR, DRS and TEM. Highlights: DyBa2 Fe3 O7.988 /DyFeO3 nanocomposites were created via ultrasound aided green synthesis. Gram-negative bacteria exhibit more responsiveness to NCS than behave Gram-positive bacteria. Uniformity of nanocomposites measurement and form can affect their antibacterial activity. The created Dy-Ba-Fe-O NCs displayed antibacterial ability. Dy-Ba-Fe-O nanocomposite has been utilized for photodegradation of dyes.